EFFORTS TO IMPROVE THE PROFESSIONALISM OF ISLAMIC RELIGIOUS EDUCATION TEACHERS THROUGH PERMANENT TEACHER FOUNDATION PROGRAM (Al-Husna Klaten Foundation Program Strategy) - Legiman, L; Rohimah , Siti (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
Teacher professionalism is an attitude of a teacher who works skillfully, agile and tenacious in communicating with students, especially during teaching and learning activities. Islamic Religious Education is a subject in madrasah which consists of subjects such as Al-Qur'an Hadith, Aqidah Akhlak, Fiqh, and Islamic Cultural History which are studied in an integrated manner. The Permanent Teacher Foundation is a program from schools/madrasas with certain conditions, rights, obligations and sanctions, which are used to form the loyalty of a teacher in private schools/madrasas. It is hoped that the Foundation's Permanent Teacher program can increase the professionalism of a teacher. This research includes qualitative research. The type of research used in this research is library research (library and field research). It is hoped that with the Permanent Teacher program at the Al-Husna Klaten Foundation, the professionalism of these teachers will increase.